Studi Karakteristik Campuran Tambalan Cepat Mantap (TCM) - Thanaya, ME., PhD, I Nyoman Arya; Jayantara, I Wayan Putra; Purbanto, I Gusti Raka (MEDIA KOMUNIKASI TEKNIK SIPIL, 2020)
Patching road pothole can be done using Permanent Cold Patching (PCP). This research main aim was to analyze the characteristic of the PCP. PCP Super Cold Mix Asphalt was used for the experiment. The mixtures were compacted Marshall hummer in lab using, and plate compactor on site. It was obtained that: compaction temperature variation significantly affected the characteristic of the mixture. Compaction at 100°C and 150°C, met stability, porosity and VMA specification, but not for the VFB. It required more compaction energy. The stability of cold compacted mixture at the age of 1 hour gave 844.74 kg (min. 500 kg). Towards this value, at the age of 48 hours; 96 hours; 192 hours; 384 hours, respectively gave increase of stability of 102%; 140%; 183%; 187% and then constant. Cold compaction on site gave less performance with porosity values in a range of 4.585-8.22% (spec. 4% -10%), therefore the VFB is less than minimum 65% of VMA; the stability obtained was 1422.72 kg (>min 500kg) or 58% stability of the samples compacted in lab at the same 16 days of age where stability had become maximum (constant). Cantabro test result of the cold mix gave 100% weight loss (the sample disintegrated), meanwhile the hot mix only lost 7.56% from 16% max loss.